RESOLUTION OF DISPUTES OVER LABOR INSPECTOR DETERMINATIONS ON OVERTIME WAGE DEFICIENCIES - Aswin Ardiansyah Huda; Budiman, Anwar; Setyowati, Retno Kus (International Peneliti Ekonomi, Sosial dan Teknologi, 2025)
Workers sometimes encounter differences in calculation with employers regarding the amount of overtime wages they should receive. In such cases, workers tend to leave the resolution of overtime wage discrepancies to labor inspectors. Labor inspectors will examine the implementation of overtime wage payments and issue a determination of the overtime wage amount. Parties who object to this determination may pursue legal remedies in the administrative court. The court's decision on the determination may result in either an acceptance (kabul) decision or a dismissal decision. These differing decisions are intriguing to analyze, as they pertain to the same administrative object but may lead to two different outcomes. The objective of this study is to analyze how labor inspector determinations in disputes over unpaid overtime wages constitute administrative decisions and to examine the legal application in resolving such disputes to provide legal certainty for both employers and workers. This study employs a normative juridical research method analyzed qualitatively. The study concludes that labor inspectors' determinations meet the criteria for administrative decisions. The application of the law through acceptance decisions provides greater legal certainty as it aligns with the fulfillment of administrative dispute criteria under statutory regulations and ensures legal certainty for both employers and workers regarding the payment of unpaid overtime wages.